THE IMPLEMENTATION OF "MANEUH DI SUNDA" LOCAL WISDOM IN CHARACTER EDUCATION AT PURWAKARTA REGENCY - Mohamad Ibrahim Adiraharja; Sri Suhartini (JOMANTARA, 2023)
The study aims to analyze the value of local culture "maneuh di sunda" in character education at Purwakarta Regency. The theory used is the theory of social construction through three elements of dialectics, namely externalization, objectivization and internalization, then strengthened by the concept of character education and local wisdom. The methodology used in this study is a qualitative approach with a case study method. Data collection techniques were observation, interviews and document studies. Interviews were conducted towards 30 respondents. Data analysis uses four stages of analysis; data collection, data reduction, data presentation, and conclusion drawing. The results showed that Sundanese local wisdom, especially the value of "maneuh di sunda" was successfully applied to elementary school students in Purwakarta Regency. This is important because in the midst of the onslaught of technological and information advances that are so rapid, students need to expose towards local wisdom-based character education. Besides to fulfill the mandate of the law, it is also to preserve local cultural values that are ancestral heritage, so that students as a generation who live in a global environment do not forget the values of their local culture. The results of this study can also be a model for other schools and other regions to be adjusted to the character of their respective local cultures.